Personality judgments from everyday images of faces - Sutherland, Clare A. M.; Rowley, Lauren E.; Amoaku, Unity T.; Daguzan, Ella; Kidd-Rossiter, Kate A.; Maceviciute, Ugne; Young, Andrew W. (Frontiers in Psychology, 2015)
People readily make personality attributions to images of strangers’ faces. Here we investigated the basis of these personality attributions as made to everyday, naturalistic face images. In a first study, we used 1,000 highly varying ‘ambient image’ face photographs to test the correspondence between personality judgments of the Big Five and dimensions known to underlie a range of facial first impressions: approachability, dominance and youthful-attractiveness. Interestingly, the facial Big Five judgments were found to separate to some extent: judgments of openness, extraversion, emotional stability and agreeableness were mainly linked to facial first impressions of approachability, whereas conscientiousness judgments involved a combination of approachability and dominance. In a second study we used average face images to investigate which main cues are used by perceivers to make impressions of the Big Five, by extracting consistent cues to impressions from the large variation in the original images. When forming impressions of strangers from highly varying, naturalistic face photographs, perceivers mainly seem to rely on broad facial cues to approachability, such as smiling.